Genome-wide identification of GATA transcription factors in tetraploid potato and expression analysis in differently colored potato flesh - Zhang, Xia; Fan, Rong; Yu, Zhuo; Du, Xuerun; Yang, Xinyue; Wang, Huiting; Xu, Wenfeng; Yu, Xiaoxia (Frontiers in Plant Science, 2024)
The GATA gene family belongs to a kind of transcriptional regulatory protein featuring a zinc finger motif, which is essential for plant growth and development. However, the identification of the GATA gene family in tetraploid potato is still not performed. In the present research, a total of 88 GATA genes in the tetraploid potato C88.v1 genome were identified by bioinformatics methods.These StGATA genes had an uneven distribution on 44 chromosomes, and the corresponding StGATA proteins were divided into four subfamilies (I-IV) based on phylogenetic analysis. The ciselements of StGATA genes were identified, including multiple cis-elements related to lightresponsive and hormone-responsive. The collinearity analysis indicates that segmental duplication is a key driving force for the expansion of GATA gene family in tetraploid potato, and that the GATA gene families of tetraploid potato and Arabidopsis share a closer evolutionary relationship than rice.The transcript profiling analysis showed that all 88 StGATA genes had tissue-specific expression, indicating that the StGATA gene family members participate in the development of multiple potato tissues. The RNA-seq analysis was also performed on the tuber flesh of two potato varieties with different color, and 18 differentially expressed GATA transcription factor genes were screened, of which eight genes were validated through qRT-PCR. In this study, we identified and characterized StGATA transcription factors in tetraploid potato for the first time, and screened differentially expressed genes in potato flesh with different color. It provides a theoretical basis for further understanding the StGATA gene family and its function in anthocyanin biosynthesis.